A construção do projeto neoliberal no Brasil (1988 - 1998): instituto liberal e o discurso da “flexibilização” e ataque às propostas de reforma agrária - Casimiro, Flávio Henrique Calheiros (Universidade Federal Rural do Rio de Janeiro, 2015)
This paper discusses the development and diffusion process of the hegemonic neoliberal project in Brazil, having the performanc e of the “organic intelectuals” of the Instituto Liberal as the object of research. The work focuses on the discursive-ideological strategies adopted by these schola rs who aimed at the construction of consense and the naturalization of the liberal neoconservative speech, around the 80s. Accordingly, we propose a discussio n around the discourse of so-called flexible labor laws and the attitude of a ttack on proposals for agrarian reform and rural social movements in Brazil. Thus o ur proposal is to discuss this neoliberal project, perceiving it as a process, as a construction whose pace and intensity of implementation are of the particularities of the Brazilian social reality. This understanding emphasizes and values the role of historical actors as real social actors, who by means of the apparatus and the dominance of private media outlets acted pedagogically for the naturalization of this worldview in Brazil.